Site pages

Current course

Participants

General

20 February - 26 February

27 February - 5 March

6 March - 12 March

13 March - 19 March

20 March - 26 March

27 March - 2 April

3 April - 9 April

10 April - 16 April

17 April - 23 April

24 April - 30 April

## Lesson 18. PURE BENDING

Module 4. Beams and bending moments
Lesson 18 PURE BENDING 18.1 IntroductionPure bending refers to flexure of a beam under a constant bending moment. Therefore, pure bending occurs only in regions of a beam where the shear force is zero. In contrast, non uniform bending refers to flexure in the presence of shear forces, which means that the bending moment changes as we move along the axis of the beam. An example of pure bending would be a beam with two couples, one on each end acting in opposite directions.
The following assumption is made in the theory of simple bending: - The material of the beam is perfectly homogeneous (i.e., of the same kind throughout) and isotropic (i.e., of equal elastic properties in all directions).
- The beam materials are stressed within its elastic limit and, thus, obey Hooks law.
- The transverse sections, which were plane before bending, remain plane after bending also.
- Each layer of the beam is free to expand or contract, independently, of the layer, above or below it.
- The value of E(Young modulus of elasticity) is the same in tension and compression
Consider a small length dx of a simply supported beam subjected to a bending moment M. Now consider two section AB and CD, which are normal to the axis of the beam RS. Due to the action of the bending moment, the beam as a whole will bend. Since we are considering a small length of dx of the beam, therefore, the curvature of the beam, in this length, is taken to be circular. A little consideration will show, that all the layer of the beam, which were originally of the same length doing not remain of the same length any more. The top layer of the beam AC has suffered compression, and reduced to A
Now we see that the layers above RS have been compressed and that bellow have stretched. The amount, by which a layer is compressed or stretched, depends upon the position of the layer with reference to RS. This layer RS, which is neither compressed nor stretched, is known as neutral plane or neutral layer. The theory of bending is called theory of simple bending.
(A) Before Bending B) After Bending
Consider a small length dx of a beam subjected to a bending moment. As a result of this moment, let this small length of beam bend into an arc of a circle with O a center. Let M= Moment acting at the beam, θ = angle subtended at the center by the arc, and R= Radius of curvature of the beam Now consider a layer PQ at a distance y from RS the neutral axis of the beam. Let this layer be compressed to P Decrease in length of this layer δl = PQ - P
^{1}Q^{1}
Strain e = (δl / Original length) = (PQ - P Now from the geometry of the curved beam, we find that the two section OP (P Or 1 - (P Or (R (PQ) - (P e = (y / R) ( e =(PQ) - (P
It is thus obvious, that the stain of a layer is proportional to its distance from the neutral axis. We also know that the stress, f = Strain X Elasticity = e.E = (y / R) x E = y x (E / R) ( e = y / R)
Since E and R are constants in this expression, therefore the stress at any point is directly proportional to y, i.e., the distance of the point from the neutral axis. The above expression may also be written as: f / y = E / R ----------(1)
The line of intersection of the neutral layer, with any normal cross-section of a beam, is known as neutral axis of the section. We have that on one side of the neutral axis there are compressive stresses, whereas on the other there are tensile stresses. At the neutral axis, there is no stress of any kind.
Let NA be the neutral axis of the section. Now consider a small layer PQ of the beam section at a distance y from the neutral axis. 18.7 Section Modulus
We have M / I=б/y=E / R M / I= б / y б or ƒ б = M / Z Z=section modulus.
`I = Moment of inertia, m^4 ,m` Z = Section modulus, m^3 , m y = Centroidal distance, m
I = b * h^3 / 12 = 1/12 b.h Z = b * h^2 / 6 = 1/6 b.h y = h / 2 I = b * h^3 / 36 = b.h Z = b * h^2 / 12 = b.h y = h / 3 I = ∏d
y = d / 2 |